2018
DOI: 10.5007/1980-0037.2018v20n4p543
|View full text |Cite
|
Sign up to set email alerts
|

Community and environment for physical activity among young people: a systematic review of the Report Card Brazil 2018

Abstract: The aim of this study was to identify evidence about the prevalence of the community and environment indicators related to physical activity (PA) among young Brazilian people. A systematic review was carried out using eight databases (PubMed, Scopus, Web of Science, LILACS, SPORTDiscus, BIREME, Scielo, and Google Scholar) with descriptors in Portuguese and English. Community and environment Indicators included access, presence, proximity, quality, safety and pollution of/in spaces, facilities, programs availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
0
10
0
5
Order By: Relevance
“…It should be noted that this mediation role ranged from approximately 14% to 32% for the three investigated perceived environmental factors, which points out to the relevance of these factors for the development of public health strategies. It is important to emphasize that a systematic review indicated that studies providing combined information between perceived and objective environmental factors were unavailable in Brazil, involving adolescents 40 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this mediation role ranged from approximately 14% to 32% for the three investigated perceived environmental factors, which points out to the relevance of these factors for the development of public health strategies. It is important to emphasize that a systematic review indicated that studies providing combined information between perceived and objective environmental factors were unavailable in Brazil, involving adolescents 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This study followed the recommendations and guidelines for conducting systematic reviews for observational studies 9 . According to the previous review 7 , the relationship between the environment and physical activity in Brazilian children and adolescents was investigated. As in the previous review, environmental characteristics related to spaces, physical activity facilities, climatic factors, pollution, and perception of the neighborhood and neighborhood were considered 7 .…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous review 7 , the relationship between the environment and physical activity in Brazilian children and adolescents was investigated. As in the previous review, environmental characteristics related to spaces, physical activity facilities, climatic factors, pollution, and perception of the neighborhood and neighborhood were considered 7 . These variables could be obtained objectively or subjectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations